2001
DOI: 10.1111/j.1469-7793.2001.00905.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo reduction in ATP cost of contraction is not related to fatigue level in stimulated rat gastrocnemius muscle

Abstract: We tested whether the reduction in ATP cost of contraction during in vivo stimulation of rat gastrocnemius muscle was related to fatigue level. Muscles (n= 44) were electrically stimulated to perform 6 min repeated isometric contractions at different frequencies; one non‐fatiguing protocol (stimulation at 0.8 Hz) and five fatiguing protocols (2, 3.2, 4, 5.2 and 7.6 Hz) were used. Anaerobic and oxidative ATP turnover rates were measured non‐invasively using 31P‐magnetic resonance spectroscopy. At the onset of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
34
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 37 publications
(56 reference statements)
5
34
0
Order By: Relevance
“…We actually found that ATP production was significantly higher in Mstn Ϫ/Ϫ animals, notably at the end of the stimulation period when glycolytic ATP production was 135% larger compared with Mstn ϩ/ϩ animals. According to the quantitative interpretation of bioenergetics data (3,13,19), this glycolytic flux enhancement was due mainly to the larger changes in pH i during the stimulation period and is in agreement with the acceleration of glucose metabolism through increased glucose uptake and utilization in Mstn Ϫ/Ϫ mouse muscle (24).…”
Section: Nssupporting
confidence: 61%
See 2 more Smart Citations
“…We actually found that ATP production was significantly higher in Mstn Ϫ/Ϫ animals, notably at the end of the stimulation period when glycolytic ATP production was 135% larger compared with Mstn ϩ/ϩ animals. According to the quantitative interpretation of bioenergetics data (3,13,19), this glycolytic flux enhancement was due mainly to the larger changes in pH i during the stimulation period and is in agreement with the acceleration of glucose metabolism through increased glucose uptake and utilization in Mstn Ϫ/Ϫ mouse muscle (24).…”
Section: Nssupporting
confidence: 61%
“…An attractive explanation for this phenomenon would lie in the shift of the fiber-type recruitment pattern since fatigue development in mixed muscle such as gastrocnemius is associated with a decreased recruitment of glycolytic fibers at the expense of oxidative fibers, which are more fatigue resistant (7,13). However, such an issue can be ruled out herein because specific force produced by Mstn Ϫ/Ϫ animals was lower as soon as the onset of the electrical stimulation period, i.e., before fatigue development.…”
Section: Nsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although data from electrically stimulated contractions consistently indicate higher ATP cost as stimulation frequency increases (2,17,20), the impact of voluntary contraction intensity on ME is less clear. Some reports suggest a positive relationship between voluntary contraction intensity and ME (70), while other reports suggest a negative relationship (34), and still others report no change in economy across intensities (3,63).…”
Section: Metabolic Economy During Voluntary Contractionsmentioning
confidence: 97%
“…With these parameters, one can estimate the energy production efficiency of the muscle, such as the speed of PCr degradation and resynthesis, provided that simultaneous force output is recorded (Giannesini et al 2001).…”
Section: P-mrs Measurements (I)mentioning
confidence: 99%